Mobile phones and nosocomial infections - Badr, Rawia Ibrahim; Badr, Hatem ibrahim; Ali, Nabil Mansour (International Journal of Infection Control, 2012)
The use of mobile phones inside hospitals especially in clinically sensitive areas is a subject of controversy because it may improve the quality of healthcare but also can transmit health care associated infections. To determine the potential role of mobile phones in harboring microorganisms and to evaluate their role in transmission of microorganisms from the mobile phone to health care personnel' hands. Thirty two staff members (12, 8 and 12 were neurosurgeons, anesthetists and nurses respectively) were enrolled in this study. A questionnaire was submitted to all participants as regard, the extent of usage of mobile phones, the location of use, the use of headsets, the awareness of disinfection practices of mobile phones and the frequency of hand washing after using their phones. They were asked to disinfect their hands using an alcohol based hand rub, fingers of both hands were cultured. Then, they were asked to do a short phone call from their personal mobile phones. Sampling was repeated from the hand used to make the call and from each participant’s mobile phone. Following the hand rub, no growth was detected of all HP' hands. After the use of a mobile phones, the rate of bacterial infection of the HP' hands increased to 30 ⁄ 32 (93.7%). The rate of mobile phone contamination was 30 ⁄ 32 (93.7%). The use of mobile phones in clinically sensitive areas should be weighed against the risk for contamination and transmission of infections. Key wordsMobile phones, Health care associated infections, questionnaire, Transmission of infection, clinically sensitive area.Corresponding author:Address: Faculty of Medicine, Mansoura University, Department of Microbiology and Immunology. Rawia I. Badr, E-mail: rawbadr@gmail.com Mobile: 0020123912852